Comparative Analysis of Chloroplast psbD Promoters in Terrestrial Plants - Shimmura, Shuichi; Nozoe, Mikio; Kitora, Shota; Kin, Satoko; Matsutani, Shigeru; Ishizaki, Yoko; Nakahira, Yoichi; Shiina, Takashi (Frontiers in Plant Science, 2017)
The transcription of photosynthesis genes encoded by the plastid genome is mainly mediated by a prokaryotic-type RNA polymerase called plastid-encoded plastid RNA polymerase (PEP). Standard PEP-dependent promoters resemble bacterial sigma-70-type promoters containing the so-called -10 and -35 elements. On the other hand, an unusual light- and stress-responsive promoter (psbD LRP) that is regulated by a 19-bp AAG-box immediately upstream of the -35 element has been mapped upstream of the psbD-psbC operon in some angiosperms. However, the occurrence of the AAG-box containing psbD LRP in plant evolution remains elusive. We have mapped the psbD promoters in eleven embryophytes at different evolutionary stages from liverworts to angiosperms. The psbD promoters were mostly mapped around 500-900 bp upstream of the psbD translational start sites, indicating that the psbD mRNAs have unusually long 5’-UTR extensions in common. The -10 elements of the psbD promoter are well-conserved in all embryophytes, but not the -35 elements. We found that the AAG-box sequences are highly conserved in angiosperms and gymnosperms except for gnetaceae plants. Furthermore, partial AAG-box-like sequences have been identified in the psbD promoters of some basal embryophytes such as moss, hornwort, and lycophyte, whereas liverwort has the standard PEP promoter without the AAG-box. These results suggest that the AAG-box sequences of the psbD LRP may have evolved from a primitive type of AAG-box of basal embryophytes. On the other hand, monilophytes (ferns) use another type of psbD promoter composed of a distinct cis-element upstream of the potential -35 element. Furthermore, we found that psbD expression is not regulated by light in gymnosperms or basal angiosperms, although they have the well-conserved AAG-box sequences. Thus, it is unlikely that acquisition of the AAG-box containing psbD promoter is directly associated with light-induced transcription of the psbD-psbC operon. Light- and stress-induced transcription may have evolved independently and multiple times during terrestrial plant evolution.